Fenofibrate Nanocrystals Embedded in Oral Strip-Films for Bioavailability Enhancement - Kevadiya, Bhavesh D. (Bioengineering (Basel), 2018)
The aim of the present study was to make a fenofibrate (FNB) nanocrystal (NC) by wet media milling, characterizations and formulates into oral strip-films (OSFs). Mechanical properties, redispersion study, and solid-state characterizations results suggested that reduction of drug crystal size at nanoscale and incorporation into OSFs does not affect the solid-state properties of the drug. In vitro dissolution kinetics showed enhanced dissolution rate was easily manipulated by changing the thickness of the OSF. In situ UV-imaging was used to monitor drug dissolution qualitatively and quantitatively in real time. Results confirm that the intrinsic dissolution rates and surface drug concentration measured with this device were in agreement with the USP-IV dissolution profiles. In vivo pharmacokinetics in rabbits showed a significant difference in the pharmacokinetics parameter (1.4 fold increase bioavailability) of FNB NC-loaded OSFs as compared to the marketed formulation “Tricor” and as-received (pristine) drug. This approach of drug nanocrystallization and incorporation into OSFs may have significant applications in cost-effective tools for bioavailability enhancement of FNB.